2020
DOI: 10.1017/s2040174420000094
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms linking exposure to preeclampsia in utero and the risk for cardiovascular disease

Abstract: Preeclampsia (PE) is now recognised as a cardiovascular risk factor for women. Emerging evidence suggests that children exposed to PE in utero may also be at increased risk of cardiovascular disease (CVD) in later life. Individuals exposed to PE in utero have higher systolic and diastolic blood pressure and higher body mass index (BMI) compared to those not exposed to PE in utero. The aim of this review is to discuss the potential mechanisms driving the relationship between PE and offspring CVD. Exposure to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 96 publications
0
38
0
Order By: Relevance
“…This concept that early physiological challenges can alter the developmental trajectories and disease risk of progeny is referred to as developmental programming. Interestingly, many of the pregnancy complications associated with shift work are also associated with metabolic, cardiovascular and endocrine disease in progeny (Godfrey & Barker, 2000;Parkinson et al 2013;Knop et al 2018;Andraweera et al 2020). However very little is known about the direct impact of maternal shift work on progeny health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept that early physiological challenges can alter the developmental trajectories and disease risk of progeny is referred to as developmental programming. Interestingly, many of the pregnancy complications associated with shift work are also associated with metabolic, cardiovascular and endocrine disease in progeny (Godfrey & Barker, 2000;Parkinson et al 2013;Knop et al 2018;Andraweera et al 2020). However very little is known about the direct impact of maternal shift work on progeny health.…”
Section: Introductionmentioning
confidence: 99%
“…2018; Andraweera et al . 2020). However very little is known about the direct impact of maternal shift work on progeny health.…”
Section: Introductionmentioning
confidence: 99%
“…4 PE is marked by abnormal placentation of the spiral arteries whereby the ischemic placenta, resultant hypoxia in the fetus, and endothelial dysfunction may lead to alterations in the morphology and function of the heart and the major vessels of the developing fetus. 5,6 In vivo studies have suggested the role of hypoxia in epicardial detachment and cardiac collagen content that may lead to alterations in cardiac shape of offspring. 5 The excess of antiangiogenic factors in utero that are triggered by placental dysfunction may possibly lead to vascular remodeling.…”
mentioning
confidence: 99%
“…Besides the immediate risk preeclampsia poses to the pregnancy, the mother and the fetus, offspring prenatally exposed to preeclampsia may be at risk for long term adverse health effects [3][4][5]. Women with a history of preeclampsia are at increased risk for long-term morbidities, including chronic hypertension, diabetes and atherosclerotic morbidity such as cardiovascular and renal disease, besides preeclampsia in future pregnancies [6][7][8].…”
Section: Introductionmentioning
confidence: 99%